2004
DOI: 10.1523/jneurosci.4870-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional Signal- and Paradigm-Dependent Linear Relationships between Synaptic Activity and Hemodynamic Responses in Rat Somatosensory Cortex

Abstract: Linear relationships between synaptic activity and hemodynamic responses are critically dependent on functional signal etiology and paradigm. To investigate these relationships, we simultaneously measured local field potentials (FPs) and optical intrinsic signals in rat somatosensory cortex while delivering a small number of electrical pulses to the hindpaw with varied stimulus intensity, number, and interstimulus interval. We used 570 and 610 nm optical signals to estimate cerebral blood volume (CBV) and oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 60 publications
9
75
0
Order By: Relevance
“…Thus we attribute the observed parenchyma patches mostly to a passive, highly local increase in [Hbr], which is attributable to an increase in oxygen extraction by the activated neurons or the surrounding glia rather than to effects of the active blood-volume response. After ϳ2 s, also at 605 nm, blood vessels became predominant because of the large CBV and CBF response, as seen in previous experiments performed on anesthetized and awake preparations (Frostig et al, 1990;Grinvald et al, 2000;Nemoto et al, 2004). To increase the SNR in the functional single-condition maps, the first 0.8 s of Figure 6 and stretched to Ϯ1.5 SD.…”
Section: Oximetric Functional Maps Estimated By Reflection Measuremenmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus we attribute the observed parenchyma patches mostly to a passive, highly local increase in [Hbr], which is attributable to an increase in oxygen extraction by the activated neurons or the surrounding glia rather than to effects of the active blood-volume response. After ϳ2 s, also at 605 nm, blood vessels became predominant because of the large CBV and CBF response, as seen in previous experiments performed on anesthetized and awake preparations (Frostig et al, 1990;Grinvald et al, 2000;Nemoto et al, 2004). To increase the SNR in the functional single-condition maps, the first 0.8 s of Figure 6 and stretched to Ϯ1.5 SD.…”
Section: Oximetric Functional Maps Estimated By Reflection Measuremenmentioning
confidence: 87%
“…Recent evidence suggests that the active vascular response (underlying the positive BOLD signal) reflects synaptic rather than spiking activity (Caesar et al, 2003a,b;Logothetis, 2003), whereas the stimulus-evoked tissue deoxygenation underlying the initial dip has been found to correlate, at least spatially, with spiking activity (Thompson et al, 2003). Furthermore, Sheth et al (2003) and Nemoto et al (2004) found that field potential measurements correlated differently with the 570 nm and the early 605 nm optical signals. This raises the question of whether some of the observed differences between the functional maps obtained using the initial hypo-oxygenation and those obtained using the CBV response might not result from a different coupling of the two hemodynamic processes to spiking and synaptic activity, respectively.…”
Section: Implications For Functional Brain Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The [HbT] signal is as rapid and spatially focused and more than an order of magnitude stronger and longer-lived. For ISOI maps, e.g., of orientation, the initial dip has been reported to give cleaner maps than the [HbT] signal, i.e., with fewer vascular artifacts (1,10 (5).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic signals are thus used extensively as proxies for such activity in functional neuroimaging techniques like fMRI and intrinsic signal optical imaging (ISOI). There has been considerable debate, however, as to which of the possible hemodynamic signals, e.g., changes in local blood oxygenation, volume, or flow, with their distinct response properties, constitutes the ''best'' signal for inferring neural activity (1,(3)(4)(5).…”
mentioning
confidence: 99%